The Bengal renaissance : identity and creativity from Rammohun Roy to Rabindranath Tagore - Dasgupta, Subrata (Delhi : Permanent Black, 2007)
Study on the social and cultural transformation as happened in 18th and 19th century Bengal, India.
Includes bibliographical references (p. [246]-261) and index.
Keywords: Social evolution; Bengal (India) -- Intellectual life -- 18th century; Bengal (India) -- Intellectual life -- 19th century